A novel exfoliated manganese phosphoselenide as a high-performance anode material for lithium ions storage - Shen, Hailin; Zhang, Wei; Zhang, Yuheng; Wang, Wei; Wang, Min; Liu, Tianyu (Frontiers in Chemistry, 2022)
Layered manganese phosphoselenide (MnPSe3) is expected to be a potential anode for Li ions storage due to it combines the merits of phosphorus with metal selenide. It promotes charge transfer and ensures a high theoretical capacity of up to 746 mA h g−1. In this work, a comprehensive study clearly demonstrated that bulk MnPSe3 electrode is the inability to maintain the integrity of the structure with severe detectable fracture or pulverization after full lithiation/delithiation, resulting in poor rate capability and cycling stability. Additionally, exfoliated few-layered MnPSe3 nanoflakes by the ultrasonic method show enhanced electrical conductivity and resistance to volume expansion. It has a high initial discharge/charge capacity reaching to 524/796 mA h g−1 and outstanding cycling stability with charge capacities of 709 mA h g−1 after 100 cycles at 0.2 A g−1 within the potential window of 0.005–3 V vs. Li+/Li. While further improving the cycles, the retention rate was still held at ∼72% after 350 cycles. This work provides new insights into exploiting new novel layered materials, such as MnPSe3 as anodes for lithium-ion batteries.